Documentation and Argument in Early China : The Shàngshū 尚書 (Venerated Documents) and the Shū Traditions - Meyer, Dirk (2021)
This study uncovers the traditions behind the formative Classic Shàngshū (Venerated Documents). It reveals a genre of “Shū” (Documents) practice that was used creatively by contrasting conceptual communities for socio-philosophical ends. Working from Warring States-manuscript texts, it shows how different communities rewrote old cultural capital, becoming political actors by expanding their scope of action through literary thought production.